Flavonoid, phenolic contents and antioxidant properties of thai hot curry paste extract and its ingredients as affected of pH, solvent types and high temperature - Settharaksa,S. (Universiti Putra Malaysia, 2015)
Spices used in curry pastes containing phenolics and flavonoids have been reported to prevent oxidative stress related diseases. Thai hot curry, Kua-khling curry paste, a Thai traditional seasoning particular Thai-Muslim, was investigated as potential functional food. In the present study, the flavonoid, phenolic contents and antioxidant activities of extract from spices used in the paste were determined. The effect of pH, solvent type and temperature (100-121°C) were investigated after the samples were extracted. It was found that the extracts of spices presented flavonoid and phenolic contents in the range 0.04-11.18 mg catechin equivalent (CE)/100 g sample and 0.68-134.91 mg gallic acid equivalent (GAE)/100g sample, respectively. Antioxidant activities determined as DPPH radical scavenging activity, hydroxyl radical scavenging activity (HRSC) and ferric reducing antioxidant power (FRAP) of the extracts were 0.49-8,214.91 mg GAE/100g sample, 0.69-9.30 mg GAE/100g sample and 25.83-6,860.55 mg GAE/100 g sample, respectively. The best solvent for extraction was water since its yielded flavonoid and phenolic contents and DPPH activityas 61.03±6.22 CE/100 g,964±79.13 GAE/100g and 1,740.84±13.57 GAE/100g, respectively. Flavonoid, phenolic contents and DPPH activity were decreased at pH lower and higher than pH 6. However, it was found that temperature at 100°C caused more depletion of flavonoids, phenolic contents and DPPH activity compared with heating 121°C. Therefore, thermally canned food may have a potential for health benefit as evaluated by antioxidant properties in vitro system.